2019
DOI: 10.1017/s1368980019001824
|View full text |Cite
|
Sign up to set email alerts
|

Are our diets getting healthier and more sustainable? Insights from the European Prospective Investigation into Cancer and Nutrition – Netherlands (EPIC-NL) cohort

Abstract: Objective:To identify differences in dietary quality, dietary greenhouse gas (GHG) emissions and food consumption over 20 years in a Dutch cohort.Design:Participants (n 8932) filled out an FFQ in 1993–1997 and in 2015. The Dutch Healthy Diet index 2015 (DHD15-index) score, GHG emissions and consumption of food groups (g/4184 kJ (1000 kcal)) were compared between the time points with paired t tests.Setting:The Netherlands.Participants:European Prospective Investigation into Cancer and Nutrition – Netherlands (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Strong product and process innovation, improving nutritional profiles (e.g., reformulation, fortification, supplementation) and environmental performance is needed to meet the 2050 GHGE target in terms of healthy and acceptable diets, taking into account price, texture, and taste. Current dietary patterns in the Netherlands are not consistent with the required GHGE targets, and specific policies may be needed to help people shift to diets with lower environmental impacts ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Strong product and process innovation, improving nutritional profiles (e.g., reformulation, fortification, supplementation) and environmental performance is needed to meet the 2050 GHGE target in terms of healthy and acceptable diets, taking into account price, texture, and taste. Current dietary patterns in the Netherlands are not consistent with the required GHGE targets, and specific policies may be needed to help people shift to diets with lower environmental impacts ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, a previous study in EPIC-NL showed dietary changes between 6 baseline and 20 years follow-up to be relatively modest. 43 Finally, the current study used the 7 Dutch LCA Database to calculate environmental indicators. It should be noted that, although 8 the LCA database is a comprehensive source of LCA indicators, there is also some 9 uncertainty in the data since they are modelled and not actually measured.…”
Section: Table 4 Descriptive Statistics Of the Environmental Impact Indicators By Quartiles Of Thementioning
confidence: 99%
“…However, a previous study in EPIC‐NL showed dietary changes between baseline and 20‐year follow‐up to be relatively modest. 61 Nevertheless, although the mean intakes of diet may have not changed substantially, individual variation could still be substantial and lead to attenuation of associations. With regard to our analyses, we need to address the possibility of residual confounding.…”
Section: Discussionmentioning
confidence: 99%